Atividade organística no Brasil: renovação ou queda de uma cultura? - Pereira, Kenny Alberto Simões [UNESP] (Universidade Estadual Paulista (Unesp), 2016)
Esta pesquisa tem por objetivo entender a forma de construção da atividade organística como uma cultura do cristianismo. Procura-se delinear os conteúdos dessa cultura e demonstrar como ela teve seus princípios geradores duradouros por tantos séculos. Em um segundo momento analisa a atividade organística no Brasil traçando seu perfil e analisando sua situação atual e suas problemática diante das novas religiosidades. Esta pesquisa procurou analisar a atividade organística no Brasil a partir dos estudos culturais tendo como principais autores teóricos Clifford Geerts, Jan Assmann e Zygmunt Bauman”

The objective of this research is to understand how the construction to perform organ music has been historically generated in Christian culture. In the first part, this thesis proposes to outline how Christian principles that have lasted for centuries were instrumental in this cultural activity.The second portion of the thesis outlines the historical trajectory of the activities and compositions of organ music in Brazil, and notes the current problems resulting from the influence of new religious beliefs on this cultural endeavor.This research and analysis of the cultural studies of organ music in Brazil follow the theoretical propositions of authors Clifford Geerts, Jan Assman, and Zygmunt Bauman.
Organ activity in Brazil: renovation ou fall of a culture?
Keywords: Órgão; História e crítica; Atividade organística no Brasil